Improved cookstove as an appropriate technology for the Logone Valley (Chad – Cameroon): Analysis of fuel and cost savings - Vaccari, Mentore; Vitali, Francesco; Mazzù, Angelo (Renewable energy, 2012)
Access to modern energy services is still low in developing countries and this lack of access affects in particular the Least Developed Countries (LDCs) and sub-Saharan Africa. The large majority of population in the Logone Valley at the border between Chad and Cameroon still relies on wood fuel burnt in smoky and inefficient fireplaces for cooking. The promotion of wood saving stoves locally produced and appropriate for the traditional cooking practices has been implemented by an international cooperation project. Two stove models were compared to the traditional 3-stone fire and a gas stove by Water Boiling Tests and Controlled Cooking Tests. The results showed significant fuel savings thanks to the use of the improved stoves. Data collected during the tests, crossed with information about the local cooking habits, allowed to estimate the impact, in term of money savings, on each household adopting an improved stove. The Centrafricain improved stove resulted being the most performing model occurring in a 25% reduction of the expenditure per family for cooking purposes in a short-medium term. This study witnesses that the use of improved wood stove is likely to be a sustainable way to achieve an appropriate minimum level of energy access for cooking purposes for the poor people in the LDCs, in particular in rural areas. ► Improved stoves dissemination can fight poor access to household energy in sub-Saharan Africa. ► Fuel savings up to 35% replacing the three-stone fire with the improved Centrafricain stove. ► Investment costs can be covered by significant money savings in less than an year. ► Scaling up is guaranteed also by income generation possibility for local handicrafts. ► The project promotes a more sustainable use of the renewable source in the region.